Modern dictionary of electronics - Graf, Rudolf F.; Elsevier Science Publishers (Boston : Newnes, 1999)
Included in this fully revised classic are well over 28,000 terms, phrases, acronyms, and abbreviations from the ever-expanding worlds of consumer electronics, optics, microelectronics, computers, communications, and medical electronics. From the basic elements of theory to the most cutting-edge circuit technology, this book explains it all in both words and pictures. For easy reference, the author has provided definitions for standard abbreviations and equations as well as tables of SI (International System of Units) units, measurements, and schematic symbols Modern Dictionary of Electronics is the bible of technology reference for readers around the world. Now fully updated by the original author, this essential, comprehensive reference book should be in the library of every engineer, technician, technical writer, hobbyist, and student.
Keywords: Electronics -- Dictionaries; Electronic books; Dictionaries